Physiological characteristics of winter cultivated plants with phytoremediation potential under the influence of of the herbicides fomesafem and sulfentrazone - Alves, Carla; Galon, Leandro; Holz, Cinthia Maethê; Kaizer, Rosilene Rodrigues; Winter, Fábio Luis; Concenço, Germani; Nonemacher, Felipe; Perin, Gismael Francisco (Revista de Ciências Agroveterinárias, 2019)
The use of plant species for phytoremediation of soil contaminated with persistent herbicides, such as inhibitors of the protoporphyrinogen oxidase enzyme (PROTOX), is an interesting alternative from the economic and environmental point of view. This work aimed to evaluate the influence of fomesafen and sulfentrazone on the characteristics related to the physiology of winter species with potential for phytoremediation of soil contaminated by these herbicides. Two experiments were installed in a greenhouse, one with the herbicide fomesafen and another with the sulfentrazone, in a randomized complete block design with four replications. Fomesafen (0.0, 0.125, 0.250, and 0.5 kg ha-1) and sulfentrazone (0.0, 0.3, 0.6, and 1.2 kg ha-1), commercial brands Flex® and Boral 500®, respectively, were applied pre-emergence on species with phytoremediation potential (black oats, vetch, turnip and lotus). The chlorophyll index, the carboxylation efficiency (EC - mol CO2 m-2 s-1), the stomatal conductance of water vapors (Gs - mol m-1 s-1), the internal CO2 concentration (Ci - μmol mol-1), the transpiration rate (E - mol H2O m-2 s-1), the amount of CO2 consumed (QT - μmol mol-1) and the water use efficiency (UEA - mol CO2 mol H2O-1), the leaf temperature ΔT (ºC), the photosynthetic rate (A - μmol m-2 s-1) and the shoot dry mass (g vase-1) were evaluated 45 days after plant emergence. It was observed that the vetch presented the best results for all evaluated variables, thus demonstrating potential to be further tested for phytoremediation of soils contaminated with the herbicides fomesafen and sulfentrazone.